Independence Functions of Stroke Patients with "Gait" Exercise - Marlina Marlina; Elly Nurachmah (Jurnal Ners, 2013)
Introduction: Stroke is a cerebro vascular disease which has clinical manifestation based on the location and the damaged lesion. The disorder of oxygen flow to the brain results clinical manifestation called hemipharese or the de fi ciency of some parts of extremities which is indicated by the muscle deficiency. Effect of exercise gait program in needed in order to recover the strength functional self care of which is indicated by the improve strength extremitas. The aimed of this study was to analyze the effect of exercise gait to the improvement of functionalself care of the patients at Sigli General Hospital in Kabupaten Pidie Nanggroe Aceh Darussalam.Methods: A quasi experimental with pretest-postest group design was used in this study. Thirty four patients were selected by using non probability sampling (consecutive sampling tehnigue) as the sample of the study. Fourteen days of exercise gait program were given to the patient. An evaluation to the result of the program was conducted after fourteen days by measuring functional self care of the subjects.Result: The statistical analysis showed that the average of the stroke patiens functional self care is significantly after the treatment (p=0.000). There was a relationship between patients age and the functional selfcare (p=0.000) and there was no relationship between sex and the functional self care (p=0.148). There was also no relationship between risk factor the functional self care (p=0.13).Conclusion: This study recommended the use of exercise gait to improve functional self care of stroke patients in order to improve their ability to do daily living activities.